The Impact of Transformational Leadership Effects on Innovative Work Behavior by the Moderating Role of Psychological Empowerment - Khan, Arif Md.; Jantan, Amer Hamzah Bin; Salleh, Lailawati Binti Mohd; Mansor, Zuraina Dato’; Islam, Md Asadul; Hosen, Sharif (Journal of Reviews on Global Economics, 2019)
The study is an endeavor to analyze the relationship between transformational leadership (TFL) and innovative work behavior (IWB) of bank employees in commercial banks of Bangladesh. This paper examines whether psychological empowerment influences the above causal relationship. Data from 372 bank employees were analyzed using Structural Equation Modeling and Partial Least Squares (SMART PLS). Our key findings suggest that there is a significant positive relationship between TFL and IWB. The results also indicate the employees who are highly psychologically empowered, like to work under TFL and this shows that when the level of psychological empowerment of employees is high, TFL impact IWB positively. From the leadership perspective, our findings suggest that the role of psychological empowerment in the relationship between TFL and IWB should not be underestimated by the leaders or the managers of the commercial banks.